EVALUATING THE SERVICE QUALITY OF BNI MANADO AUTOMATED TELLER MACHINE (ATM) USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Baroleh, Zefanya Fernando; Tumiwa, Johan (Universitas Sam Ratulangi, 2016)
One of the innovation from bank industry is Automated Teller Machine (ATM). With the increasing number of customer using the facilities of ATM, the service quality of ATM should be improve. This research is conducted in order to analyze the importance of service quality and how is the performance of the service quality of BNI Manado ATM using Importance and Performance Analysis. There are 50 users of BNI ATM Manado taken as the sample of this research by using purposive sampling./Result of this research reveals that the behavior of the ATM staffs is the only attributes that is very important and the performance level is also high while others attributes have high importance but low performance, low importance but high performance and low importance along with low performance. From that result, the researcher suggests that the management of BNI Manado should allocating and focusing the resources of unimportant attributes to the more important attributes. Keywords: service quality, importance and performance analysis, bank